Alumina fiber reinforced MAX-phase medium-entropy ceramic-based composite material as well as preparation method and application thereof

By introducing alumina fibers into the MAX-phase ceramic materials and using ball milling, pre-pressing and hot-pressing sintering methods, high-strength MAX-phase entropy ceramic matrix composite materials were prepared, which solved the problem of insufficient strength of the MAX-phase ceramic materials and significantly improved its application performance.

CN119797924APending Publication Date: 2025-04-11HEFEI INNOVATION RES INST BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411842450.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The low hardness and strength of MAX-phase ceramic materials limit their use in practical applications.

Method used

The preparation method of entropy ceramic matrix composite in the MAX phase is adopted to prepare a composite material with excellent mechanical properties through ball mill mixing, pre-pressing molding and hot-pressing sintering.

Benefits of technology

It improves the fracture toughness and bending strength of entropy ceramic materials in the MAX phase, and expands its application possibilities in the fields of high-temperature seals, nuclear fuel cladding materials, brushes and electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188261650000071
    Figure BDA0005188261650000071
Patent Text Reader

Abstract

The invention relates to the field of MAX-phase ceramic-based composite materials, in particular to an alumina fiber reinforced MAX-phase medium-entropy ceramic material-based composite material and a preparation method thereof. According to the method, the MAX-phase medium-entropy ceramic material is synthesized by adopting the high-entropy effect, the comprehensive performance of the MAX-phase medium-entropy ceramic material is further improved through the effects such as solution strengthening and lattice distortion caused by high entropy, and more possibilities are provided for application of the MAX-phase medium-entropy ceramic material in actual engineering. On the basis of an entropy ceramic material in a MAX phase, alumina fiber is introduced as a second phase, synthesis is carried out by means of pressure sintering and the like, performance improvement of one plus one greater than two is achieved by means of performance complementation, structural fusion and the like while the performance of each material is maintained, the comprehensive performance of entropy ceramic in a single MAX phase is effectively improved, and the performance of the entropy ceramic is improved. And the method can be applied to practical engineering application more easily.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medium-entropy ceramic preparation, and more specifically, relates to an alumina fiber reinforced MAX phase medium-entropy ceramic material-based composite material and a preparation method and application thereof. Background Art

[0002] MAX phase ceramic materials have the advantages of both metals and ceramics, and have broad application prospects. They are expected to be used in high-temperature seals, nuclear fuel cladding materials, new brushes and electrodes, etc. However, compared with traditional ceramic materials, MAX phase ceramic materials have lower hardness and strength, which greatly limits their practical application. Therefore, how to prepare high-strength MAX phase medium-entropy ceramic composites is a technical problem that needs to be solved urgently. Summary of the invention

[0003] In order to further improve the comprehensive performance of MAX phase ceramic materials, the present invention provides a method for preparing an alumina fiber reinforced MAX phase medium entropy ceramic-based composite material, and the composite material prepared by the method has excellent comprehensive mechanical properties, such as excellent fracture toughness and bending strength.

[0004] Based on the above purpose, the present invention adopts the following technical solution:

[0005] A method for preparing an alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material, the method comprising the following steps:

[0006] (1) mixing Ti2AlC, V2AlC, Cr2AlC, grinding balls and grinding aids by ball milling, and dispersing the obtained mixed powder and alumina fibers in a dispersing aid and a dispersing medium to obtain a mixture;

[0007] (2) pre-pressing the mixture in step (1) to obtain a ceramic blank;

[0008] (3) hot pressing and sintering the ceramic blank in step (2) to obtain the composite material.

[0009] According to an embodiment of the present invention, the composite material has a MAX phase material as a matrix and alumina fibers as a toughening phase;

[0010] The MAX phase materials include Ti2AlC, V2AlC and Cr2AlC.

[0011] According to an embodiment of the present invention, in step (1), the purity of the alumina fiber is ≥98%, the diameter is 0.1-0.6 μm, and the length is 50-100 μm.

[0012] According to an embodiment of the present invention, in step (1), the particle size of the mixed powder is not greater than 50 μm, and the purity is not less than 99%.

[0013] According to an embodiment of the present invention, in step (1), the dispersion medium is ethanol, such as anhydrous ethanol.

[0014] According to an embodiment of the present invention, in step (1), the mass ratio of alumina fiber to dispersion medium is 1:(20-40), for example, 1:20, 1:25, 1:30, 1:35 or 1:40.

[0015] According to an embodiment of the present invention, in step (1), the dispersing aid is sodium hexametaphosphate.

[0016] According to an embodiment of the present invention, in step (1), the amount of the dispersing aid is 1 to 3% of the mass of the alumina fiber, for example, 1%, 2% or 3%. Preferably, ultrasonic dispersion is adopted, for example, a glass rod is used to assist stirring during the ultrasonic dispersion process.

[0017] According to an embodiment of the present invention, in step (1), the molar ratio of Ti2AlC, V2AlC and Cr2AlC is (0.8-1.2):(0.8-1.2):(0.8-1.2).

[0018] According to an embodiment of the present invention, in step (1), the mass of the alumina fiber is 10wt% to 30wt% of the total mass of the mixed powder, for example, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.

[0019] According to the embodiment of the present invention, in step (1), the ball-to-material ratio is (5-10):1, the ball milling speed is 200-400 rpm / min, the ball milling time is 6-10 h; and the grinding balls are agate balls.

[0020] According to an embodiment of the present invention, in step (1), the grinding aid is anhydrous ethanol.

[0021] According to an embodiment of the present invention, in step (1), the temperature during ball milling is 25-45° C., and the ball milling time is 4 to 6 hours.

[0022] According to an embodiment of the present invention, in step (1), the size of the mixture is 125-150 mesh.

[0023] According to an embodiment of the present invention, in step (1), after the obtained mixed powder and alumina fibers are dispersed in a dispersing aid and a dispersing medium, they may be dried to obtain the mixture.

[0024] Preferably, the drying is vacuum drying, for example. Preferably, the pressure of the vacuum drying is less than 0.1 MPa, the temperature of the vacuum drying is 60-80° C., and the drying time is 12-24 h.

[0025] According to an embodiment of the present invention, in step (2), the pre-pressing molding equipment is a hydraulic press, and the molding pressure is 5-15MPa, preferably 8-12MPa, for example, 10MPa; the holding time during the molding process is 1-10min, preferably 1-5min, for example, 1min.

[0026] According to an embodiment of the present invention, in step (3), the hot pressing sintering conditions are: under vacuum or argon atmosphere, the sintering pressure is 10-50MPa, preferably 30-50MPa, the sintering temperature is 550-1550°C, preferably 1100-1400°C; the sintering insulation time is 120-210min.

[0027] According to an embodiment of the present invention, the method further comprises a post-treatment step (4) for removing impurities from the prepared product.

[0028] As an exemplary embodiment of the present invention, the method for preparing the composite material comprises:

[0029] a. Ti2AlC, V2AlC, Cr2AlC, grinding balls and grinding aids were ball-milled to obtain a mixed powder, and then the alumina fibers were poured into a dispersion medium containing a dispersing aid for ultrasonic dispersion, and then the mixed powder was added to the dispersion for magnetic stirring, and vacuum dried, and then sieved to obtain a mixture;

[0030] b. The resulting mixture is placed in a hydraulic press for pre-pressing to obtain a ceramic embryo;

[0031] c. The obtained ceramic embryo is placed in a graphite mold and hot-pressed and sintered under vacuum at a sintering temperature of 550 to 1550°C and a sintering pressure of 10 to 50 MPa;

[0032] d. The MAX phase block obtained by sintering is machined to remove the impurity-containing surface to obtain an alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material.

[0033] The present invention also provides an alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material prepared by the above method.

[0034] The present invention also provides application of the composite material in high-temperature seals, nuclear fuel cladding materials, brushes and electrodes.

[0035] Beneficial effects of the present invention:

[0036] The present invention adopts the "high entropy effect" to synthesize MAX phase medium entropy ceramic materials (i.e., mixed powders). The solid solution strengthening and lattice distortion effects caused by the increase in entropy further enhance the comprehensive performance of MAX phase medium entropy ceramic materials, providing more possibilities for the application of MAX phase medium entropy ceramic materials in practical engineering. On the basis of MAX phase medium entropy ceramic materials (i.e., mixed powders), alumina fibers are introduced as the second phase and synthesized by means of pressure sintering, while maintaining the properties of each material, a performance improvement of one plus one greater than two is achieved through performance complementarity and structural fusion, effectively improving the comprehensive performance of a single MAX phase medium entropy ceramic, making it easier to put into practical engineering applications. The details are as follows:

[0037] (1) The method of the present invention makes full use of the synthesis method of vacuum hot pressing sintering, so that the uniformly mixed raw materials can be used to prepare composite materials at a lower temperature, thereby reducing energy loss.

[0038] (2) The method of the present invention uses alumina fibers to enhance the strength of composite materials. Alumina fibers are cheap and have high strength. By compounding alumina fibers with MAX phase intermediate entropy materials (such as Ti2AlC, V2AlC and Cr2AlC), the strength of the MAX phase intermediate entropy materials can be effectively improved, thereby expanding the application field of the MAX phase intermediate entropy materials. DETAILED DESCRIPTION

[0039] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0040] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0041] Comparative Example 1

[0042] The method for preparing Ti2AlC powder material by pressureless sintering using Ti powder, Al powder and graphite powder as reaction raw materials comprises the following steps:

[0043] a. Ingredients: First, weigh the raw materials (Ti powder, Al powder and graphite powder) according to the molar ratio of Ti:Al:C=2:x (x=1.1-1.3):1, and stir and mix them evenly. Add alcohol to the evenly mixed powders and wet-mill for 20-40 minutes to form a more evenly mixed raw material slurry; vacuum dry the slurry, and dry-mill the powder obtained after drying with a ball mill for 5-15 minutes;

[0044] b. Sintering: Place the pressed embryo into a tubular furnace for pressureless sintering; the sintering temperature is 1150°C and the holding time is 180 minutes.

[0045] c. Machining: The Ti2AlC powder obtained by sintering is finely ground to obtain micron-sized powder.

[0046] Comparative Example 2

[0047] The method for synthesizing MAX phase medium entropy ceramic material by vacuum hot pressing sintering method using Ti2AlC, V2AlC, Cr2AlC MAX phase powder as reaction raw materials comprises the following steps:

[0048] a. The MAX phase powders of Ti2AlC, V2AlC and Cr2AlC in equal molar ratios were mixed by ball milling, then vacuum dried and sieved.

[0049] b. The obtained mixed raw materials are placed in a hydraulic press for pre-pressing to obtain a ceramic embryo. The pressing pressure is 10 MPa and the holding time is 1 min.

[0050] c. The obtained ceramic blank is placed in a graphite mold and hot-pressed and sintered in a vacuum environment at a sintering temperature of 1200°C and a sintering pressure of 30 MPa.

[0051] d. The MAX phase block obtained by sintering is machined to remove the impurity-containing surface to obtain a MAX phase medium-entropy ceramic material.

[0052] Example 1

[0053] The method for synthesizing alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material by vacuum hot pressing sintering method using Ti2AlC, V2AlC, Cr2AlC and alumina fiber as raw materials comprises the following steps:

[0054] a. Ti2AlC, V2AlC and Cr2AlC in equal molar ratios are prepared, and grinding balls and anhydrous ethanol as a grinding aid are added for ball milling to obtain a mixed powder. Then, 30wt% alumina fiber (based on the mixed powder), the diameter of the alumina fiber is 0.1-0.6μm, and the length is 50-100μm, is poured into anhydrous ethanol containing a dispersing aid sodium hexametaphosphate as a dispersing medium for ultrasonic dispersion. The mixed powder obtained is then added to the above-mentioned dispersion for magnetic stirring, vacuum drying, and then sieved to obtain a mixture with a particle size of about 45μm, wherein the mass ratio of alumina fiber to dispersing medium is 1:30; the amount of the dispersing aid is 2% of the mass of the alumina fiber.

[0055] b. The obtained mixed raw materials are placed in a hydraulic press for pre-pressing to obtain a ceramic embryo. The pre-pressing pressure is 12 MPa and the holding time is 1 min.

[0056] c. The obtained ceramic embryo is placed in a graphite mold and hot-pressed and sintered in a vacuum environment at a sintering temperature of 1100°C, a sintering pressure of 50 MPa, and a holding time of 180 min.

[0057] d. The MAX phase block obtained by sintering is machined to remove the impurity-containing surface to obtain an alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material.

[0058] Example 2

[0059] The method for synthesizing alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material by using Ti2AlC, V2AlC, Cr2AlC MAX phase powder and alumina fiber as raw materials and vacuum hot pressing sintering method comprises the following steps:

[0060] a. Ti2AlC, V2AlC, Cr2AlC MAX phase powders in equal molar ratios are prepared, and grinding balls and anhydrous ethanol as a grinding aid are added for ball milling to obtain a mixed powder. Then, 30wt% alumina fiber (based on the mixed powder) with a diameter of 0.1-0.6μm and a length of 50-100μm is poured into anhydrous ethanol containing a dispersing aid sodium hexametaphosphate as a dispersing medium for ultrasonic dispersion. The mixed powder obtained is then added to the above-mentioned dispersion for magnetic stirring, vacuum drying, and then sieving to obtain a mixture with a particle size of about 45μm; wherein the mass ratio of alumina fiber to dispersing medium is 1:30; and the amount of dispersing aid used is 2% of the mass of alumina fiber.

[0061] b. The obtained mixed raw materials are placed in a hydraulic press for pre-pressing to obtain a ceramic embryo. The pre-pressing pressure is 12 MPa and the holding time is 1 min.

[0062] c. The obtained ceramic blank is placed in a graphite mold and hot-pressed and sintered in a vacuum environment at a sintering temperature of 1200°C, a sintering pressure of 30 MPa, and a holding time of 180 min.

[0063] d. The MAX phase block obtained by sintering is machined to remove the impurity-containing surface to obtain an alumina fiber reinforced MAX phase medium entropy ceramic matrix composite material.

[0064] Test Case

[0065] The products prepared in Example 1-2 and Comparative Example 1-2 were subjected to strength testing. The testing method was to cut the samples into cylindrical specimens with a height-to-diameter ratio of 2:1 using wire cutting, and polish the surfaces thereof. The mechanical properties of the specimens were tested using a universal material testing machine.

[0066] The test results are shown in Table 1 below:

[0067] Table 1

[0068]

[0069] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material based on alumina fiber reinforced MAX phase medium entropy ceramic material, characterized in that: The method comprises the following steps: (1) mixing Ti2AlC, V2AlC, Cr2AlC, grinding balls and grinding aids by ball milling, and dispersing the obtained mixed powder and alumina fibers in a dispersing aid and a dispersing medium to obtain a mixture; (2) pre-pressing the mixture in step (1) to obtain a ceramic blank; (3) hot pressing and sintering the ceramic blank in step (2) to obtain the composite material.

2. The method according to claim 1, characterized in that The composite material has MAX phase material as a matrix and alumina fiber as a toughening phase; The MAX material phases include Ti2AlC, V2AlC and Cr2AlC.

3. The method according to claim 1, characterized in that The purity of the alumina fiber is ≥98%, the diameter is 0.1-0.6 μm, and the length is 50-100 μm.

4. The method according to claim 1, characterized in that: The particle size of the mixed powder is not greater than 50 μm, and the purity is not less than 99%.

5. The method according to claim 1, characterized in that The dispersing aid is sodium hexametaphosphate; Preferably, the amount of the dispersing aid is 1 to 3% of the mass of the alumina fiber.

6. The method according to claim 1, characterized in that The ball-to-material ratio in the ball milling mixture is (5-10):1, the ball milling speed is 200-400 rpm / min, the ball milling time is 6-10 hours, and the grinding balls are agate balls; Preferably, the grinding aid is anhydrous ethanol, the temperature during ball milling is 25-45° C., and the ball milling time is 4 to 6 hours.

7. The method according to claim 1, characterized in that In step (1), the obtained mixed powder and alumina fibers are dispersed in a dispersing aid and a dispersing medium, and then dried to obtain the mixture; Preferably, the drying method is vacuum drying; Preferably, the vacuum drying pressure is less than 0.1 MPa, the vacuum drying temperature is 60-80° C., and the drying time is 12-24 h.

8. The method according to claim 1, characterized in that The pre-pressing molding equipment is a hydraulic press with a molding pressure of 5-15 MPa; The holding time during the molding process is 1-10 minutes.

9. The method according to claim 1, characterized in that: The hot pressing sintering conditions are: in a vacuum or argon atmosphere, the sintering pressure is 10-50 MPa, and the sintering temperature is 550-1550° C.

10. Use of the composite material prepared by the method according to any one of claims 1 to 9 in high-temperature seals, nuclear fuel cladding materials, brushes or electrodes.